Older Adults' Perception on and Use of Patient Portals: A Comparative Analysis of Two Samples. Issue 1 (January 2022) - Son, Hyojin; Nahm, Eun-Shim; Zhu, Shijun; Galik, Elizabeth; Van de Castle, Barbara; Seidl, Kristin L.; Russomanno, Vince
Abstract : Older adults can benefit from using patient portals. Little is known whether perception of and use of patient portals differ among older adults in diverse healthcare contexts. This study analyzed the difference in perceived usability, self-efficacy, and use of patient portals between older adults recruited from a healthcare system (n = 174) and older adults recruited from nationwide communities (n = 126). A secondary data analysis was conducted using the data sets of two independent studies. A series of linear and ordinal logistic regression analyses were performed. The healthcare system sample had more health issues, higher levels of perceived usability and self-efficacy, and frequent use of patient portals compared with the community sample. This study indicates that efforts to improve usability of patient portals and self-efficacy are essential for all older adult users. The association between perceived usability and patient portal use was stronger in the community sample than in the healthcare system sample, suggesting that approaches to support older adults' efficient use of patient portals should be tailored to their health status and care needs. Future studies may include inpatient and outpatient portals and investigate the impact on health outcomes of older adults across care settings.